The Recurring Resonance Of Philip Roth’s The Plot Against America: Adaptations Across Streaming, Novel, And The American Political Landscape (Journal of Namibian Studies : History Politics Culture, 2022)
The Plot Against America is considered to be Philip Roth’s take on the Jewish uncertainty and the looming restlessness and fear that pertained Jewish families during the times of the holocaust set in an alternate universe where Charles A. Lindberg, supposedly a Nazi sympathizer gets elected as the president of the United States. Roth situates the Jewish experience as one riddled with uncertainty and a ‘perpetual fear’, as the title of the last chapter in the novel indicates. The novel functions as a treatise on the constant trepidation of the Jewish experience. Written in 2004, as a historical alternative fiction, the novel received critical acclaim keeping in tradition with most of Roth’s writings. Roth’s impeccable artistry takes us into experiencing a large and varied set of perceptions through several characters poised at different ends of the Jewish spectrum. However, when this novel was adapted into an HBO limited series during 2020 by the creator duo David Simon and Ed Burns, the inherent subtext of the story extended its relevance and opprobrium to that of the then contemporary American political landscape. The paper explores an intermedial study of how the text was seen in a new light, as the Jewish fear could now be drawn as an allusion to that of the recent concerns that perpetrated within the minorities of the country, the liberals, immigrants, especially the Arabs and Muslims within Trump’s America.